Viability and survival of Scleortium oryzae Catt. incitant of stem rot of rice preserved in the laboratory vis-Ã -vis over wintering under natural field condition in Manipur - GOPAL KUMAR NIRUOLA CHHETRY, JITEN KONTHOUJAM* and (Indian Phytopathology, 2005)
Sclerotium oryzae.Catt. the incitant of stem rot of rice produce enormous quantity of sclerotia in the field. Formation of sclerotia was initiated at crop maturity and harvesting inside the stems of infected plants and progressed inside their left over stubbles during the off-season. 92% of fresh sclerotia inside infected stems at harvesting germinated readily within 1-2 days on PDA incubated at 27 + 1 0 C. However, only 87 % of sclerotia collected the next month from left over stubbles in the same sick fields germinated. Viability further declined to 42% during the next nine months (9) after harvest ,when over wintering sclerotia are accumulated in field scum. Sclerotia in their free state were less viable than those over wintering naturally inside left over stubbles or in degenerated plant tissue debris in the top soil in the fields. Viability decreased with age in all the isolates collected from different sources. Age and over wintering medium of sclerotia did not have any significant effect on their vigor in germination and formation of fresh sclerotia in in-vitro.